Perspective of Rural People in Western Ghats for Self-Sustaining: Case Study in Areas Adjoining Kudremukh National Park - Manohar Muthyala, Prashanth (Digital Repository of Theses, 2024)
The Western Ghats, a biodiversity hotspot in India, is home to many Indigenous communities who have traditionally relied on self-sustenance practices for their livelihoods. However, with increasing pressure on resources due to population growth and development, these practices are being threatened. This study aims to understand the impact of self-sustenance practices on the livelihoods of communities in the Western Ghats. The study collected data on various self-sustenance practices such as agriculture, forestry, and non-timber forest products, and analyzed the data using descriptive statistics and regression analysis. The results showed that self-sustenance practices have a positive impact on the livelihoods of communities in the Western Ghats, with agriculture and forestry being the most important contributors. However, the study also found that these practices are being threatened by factors such as land conversion and degradation. Success of an opportunity itself is finding the right suitable opportunity. Communities in the rural background walk the path of choosing the right opportunity with time evaluated and experience-based process. The study concludes that promoting and protecting self- sustenance practices is crucial for the livelihoods of communities in the Western Ghats and for the conservation of the region's biodiversity. The Western Ghats, a UNESCO World Heritage site, is one of the most biodiverse regions in India, home to a wide variety of flora and fauna (Lakhanpal, 2019). The region is also home to many Indigenous communities who have traditionally relied on self-sustenance practices such as agriculture, forestry, and non- vii timber forest products (NTFPs) for their livelihoods. However, with increasing pressure on resources due to population growth and development, these practices are being threatened. 1.1 Method The study collected data on self-sustenance practices from a sample of communities in the Western Ghats using a combination of surveys and interviews. The data was analyzed using descriptive statistics and regression analysis, adopting Constructivist Grounded Theory (CGT) a research methodology that combines the principles of constructivism and grounded theory. Constructivism is a philosophical stance that posits that knowledge is constructed through human interaction with the world and that individuals actively construct their own understanding of reality. Grounded theory, on the other hand, is a research methodology that emphasizes the discovery of theory through the analysis of data. CGT is a qualitative research approach that focuses on the discovery of new theory through the analysis of data collected from participants. It emphasizes the importance of the researcher's own perspective and the active construction of meaning by the researcher and participants (Charmaz, 2017). In CGT, data collection and analysis are done simultaneously, with the researcher continuously comparing new data with existing data and theories, allowing for the emergence of new concepts and themes. The goal is to generate a theory that is grounded in the data and that reflects the perspectives of the participants. CGT is often used in fields such as sociology, psychology, and education, where the focus is on understanding human behavior and experiences. It is particularly useful for studying complex social phenomena, viii as it allows for the discovery of new theories and concepts that reflect the perspectives of the participants. 1.2 Introduction The results showed that self-sustenance practices have a positive impact on the livelihoods of communities in the Western Ghats, with agriculture and forestry being the most important contributors. However, the study also found that these practices are being threatened by factors such as land conversion and degradation. 1.3 Discussion and Conclusion The study concludes that promoting and protecting self-sustenance practices is crucial for the livelihoods of communities in the Western Ghats and for the conservation of the region's biodiversity. This could include measures such as community-based resource management, sustainable land use planning, and policies to support traditional livelihoods.